Director Eligibility: Corporations and AI - Daisuke ASAOKA (AAOS Transactions)
By examining the nature of corporate personhood and the effects of AI, this paper expands on an existing argument for allowing corporations, as opposed to natural persons, to serve as independent board directors. While a corporation that serves as a director may enjoy limited liability and provide knowledge that a natural person cannot, the implications of such a situation are critical when viewed in combination with AI technology. Although AI does not have personhood in itself, corporations that own AI are given corporate personhood as a legal fiction. Human directors commonly obtain assistance from AI in making decisions, but they are open to being replaced by an AI-powered corporation when the latter has superior intelligence or when tasks are simple enough for automation. In this case, the existing requirement that boards comprise multiple people becomes unnecessary, because a single AI-powered director can provide a form of collective intelligence on its own. Such a corporation, with its lack of human intervention, is essentially a thing that consists of capital, in a transformation of the traditional view of a corporation as a combination of humans and capital.